Inter-cohort growth for three tropical resources: tilapia, octopus and lobster - Velázquez-Abunader, Iván (Universidad de Costa Rica, 2015)
Growth parameters are an important component for the stock assessment of exploited aquatic species. However, it is often difficult to apply direct methods to estimate growth and to analyse the differences between males and females, particularly in tropical areas. The objective of this study was to analyse the inter-cohort growth of three tropical resources and discuss the possible fisheries management implications. A simple method was used to compare individual growth curves obtained from length frequency distribution analysis, illustrated by case studies of three tropical species from different aquatic environments: tilapia (Oreochromis aureus), red octopus (Octopus maya) and the Caribbean spiny lobster (Panulirus argus). The analysis undertaken compared the size distribution of males and females of a given cohort through modal progression analysis. The technique used proved to be useful for highlighting the differences in growth between females and males of a specific cohort. The potential effect of extrinsic and intrinsic factors on the organism’s development as reflected in the size distribution of the cohorts is discussed.